Analisis Sistem Pengendalian Intern Atas Penjualan Kredit Pada UD. Mitra Aluminium Surabaya - Vincentius Timoti, Yosia; Setyarani, Yulia (Rifa'Institute, 2023)
The Internal Control System is a process carried out by the board of commissioners, management and other entities that is designed to provide reasonable assurance about the achievements in the reliability of financial reporting, the effectiveness and efficiency of operations and compliance with applicable laws and regulations. But in this case there are still many companies that ignore the importance of internal control for the company. This study aims to analyze the internal control system on credit sales at UD. Mitra Aluminium. This study uses a qualitative method with the research object UD. Mitra Aluminium, which is a trading company whose main activity is to buy goods from suppliers and resell them to consumers without changing or changing the physical form of the goods. Sources of data in this study were obtained through interviews, observation, and documentation. The results of this study indicate that the internal control system for credit sales at UD. Mitra Aluminum is still not optimal because there are still many mistakes found in the division of employee tasks, the credit sales system is still not right, so there are still many unpaid credit and supervision in operational activities is not optimal. Therefore, researchers provide recommendations that can improve internal control over credit sales at UD. Mitra Aluminum, namely conducting an analysis on customers before making payments on credit, providing a security deposit system to prevent bad credit.